Geoespacialização da favorabilidade climática à ocorrência de giberela e brusone do trigo no Cerrado brasileiro. - Doracenzi, Eduardo Lopes (2024)
Wheat is a cereal of great importance in human nutrition and plays a crucial role in global food security, representing 30% of world grain production. Cultivated extensively around the world, it is the second most consumed food and provides a significant source of calories, protein and essential nutrients for millions of people. World wheat production is economically and socially relevant, with a cultivated area that exceeds 222 million hectares and a total production of 789.5 million tons of grains in the 2022/23 harvest. In Brazil, the 14th largest producer, wheat is cultivated mainly in the South, Southeast and Center-West regions, covering more than 90% of the cultivated area and national production. In recent years, the country has recorded record increases in production, driven by high domestic demand, expanding the wheat agricultural frontier to the Brazilian Cerrado regions, mainly in the states of Bahia, Goiás, Distrito Federal and Minas Gerais. Despite the favorable soil and climate conditions of the Cerrado, the favorable climate and different growing regions in the country can also provide favorable conditions for the development of diseases, such as Fusarium head blight (Gibberella zeae) and blast (Pyricularia oryzae), which can compromise quality and crop productivity. In this context, the mapping and spatialization of climatic conditions and the assessment of the favorability for the occurrence of these diseases can be fundamental to improving the understanding of the dynamics between pathogens and local edaphoclimatic characteristics, helping to make decisions about effective management strategies. The objective of this study was to analyze the distribution of climatic favorability for the occurrence of Fusarium head blight and wheat blast in the Cerrado, in addition to understanding the effect of the dynamics of different planting times in these conditions. The results obtained offer a comprehensive view of the geographic and temporal dynamics of favorable conditions for diseases. It was observed that most Cerrado areas present favorable conditions for the development of Fusarium head blight and wheat blast and the planting time has an influence on the infection period during which the diseases develop. The critical periods of favor for the occurrence of FHB will be in the months of July, August and September; It is recommended to plant an early cycle in March or a late cycle in May to reduce the likelihood of the disease occurring. Plantings carried out in March, April and May present the months of August and September with higher rates of climate favorability for blast infections. The spatialization of climate favorability classes for the occurrence of diseases is an important strategy for planning, making assertive decisions in integrated management and improving both productivity and production quality.